2022
DOI: 10.1002/cncr.34083
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cisplatin with or without imatinib in advanced chordoma: A retrospective case‐series analysis from the Italian Rare Cancers Network

Abstract: Background To report on a retrospective case‐series analysis of weekly cisplatin (wCDDP) as a single agent or combined with imatinib (wCDDP/I) in patients with advanced chordoma treated within the Italian Rare Cancer Network. Methods Adult patients with a diagnosis of advanced, brachyury‐positive chordoma, treated from April 2007 to October 2020 with wCDDP or wCDDP/I were retrospectively identified. Imatinib was withheld at the same time as wCDDP. Response according to Response Evaluation Criteria in Solid Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…42 Standard anthracycline chemotherapy is effective in soft-tissue tumors and osteosarcoma but exhibits limited efficacy in chordoma, 8 and cisplatin has been utilized to treat chordoma on the basis of the findings of limited retrospective series and case reports. 43 Moreover, research indicates the involvement of EP300 and vimentin in drug resistance across various tumor cells, [44][45][46][47][48] leading to the development of targeted inhibitors. This identifies them as potential targets for overcoming chemoresistance in tumor treatment.…”
Section: Fig 5 Sgc-cbp30 and C646mentioning
confidence: 99%
“…42 Standard anthracycline chemotherapy is effective in soft-tissue tumors and osteosarcoma but exhibits limited efficacy in chordoma, 8 and cisplatin has been utilized to treat chordoma on the basis of the findings of limited retrospective series and case reports. 43 Moreover, research indicates the involvement of EP300 and vimentin in drug resistance across various tumor cells, [44][45][46][47][48] leading to the development of targeted inhibitors. This identifies them as potential targets for overcoming chemoresistance in tumor treatment.…”
Section: Fig 5 Sgc-cbp30 and C646mentioning
confidence: 99%
“…NCCN guidelines recommend that targeted therapy can be used for the systemic treatment of chordoma. Imatinib (Adenis et al 2013;Baldi et al 2022;Hindi et al 2015;Stacchiotti et al 2009Stacchiotti et al , 2018, dasatinib (Verma et al 2020), sorafenib (Schuetze et al 2017;Bompas et al 2015), sunitinib, and lapatinib (Lebellec et al 2016a) have shown significant clinical efficacy. Thalidomide (Stacchiotti et al 2013;Chay et al 2011;Rehlinghaus et al 2012) is effective for drug-resistant chordomas, but severe toxicity limits its clinical application.…”
Section: Targeted Therapymentioning
confidence: 99%